2014
DOI: 10.1063/1.4885415
|View full text |Cite
|
Sign up to set email alerts
|

Density dependence of the room temperature thermal conductivity of atomic layer deposition-grown amorphous alumina (Al2O3)

Abstract: We report on the thermal conductivity of atomic layer deposition-grown amorphous alumina thin films as a function of atomic density. Using time domain thermoreflectance, we measure the thermal conductivity of the thin alumina films at room temperature. The thermal conductivities vary ∼35% for a nearly 15% change in atomic density and are substrate independent. No density dependence of the longitudinal sound speeds is observed with picosecond acoustics. The density dependence of the thermal conductivity agrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 36 publications
10
49
1
Order By: Relevance
“…319 The reported thermal conductivities for poly-crystalline 254,320 and amorphous [57][58][59]321 Al 2 O 3 of 16-33 and 0.7-2.6 W/mK, respectively, are also comparable to the previously discussed lower range reported for AlN and amorphous SiO 2 (see Table VIII Regarding HfO 2 , we are unaware of any reports of thermal conductivity for single-crystal hafnia. Investigations of bulk ceramic or sputter deposited thin film poly-crystalline hafnia doped/stabilized with yttria for thermal barrier coating applications have reported relatively low thermal conductivities of 1.5-2.0 W/mK.…”
Section: 283supporting
confidence: 58%
See 3 more Smart Citations
“…319 The reported thermal conductivities for poly-crystalline 254,320 and amorphous [57][58][59]321 Al 2 O 3 of 16-33 and 0.7-2.6 W/mK, respectively, are also comparable to the previously discussed lower range reported for AlN and amorphous SiO 2 (see Table VIII Regarding HfO 2 , we are unaware of any reports of thermal conductivity for single-crystal hafnia. Investigations of bulk ceramic or sputter deposited thin film poly-crystalline hafnia doped/stabilized with yttria for thermal barrier coating applications have reported relatively low thermal conductivities of 1.5-2.0 W/mK.…”
Section: 283supporting
confidence: 58%
“…44,45 For such devices, knowledge of properties such as Young's modulus and film stress are critical for predicting the flexure and resonance frequencies of bridged and cantilevered switches and sensors, [46][47][48][49] stretched transistor device performance, 50,51 buckling failures in nanopatterned structures, 52,53 and macroscale buckling and nanoscale wrinkling effects for stiff high-k films deposited on compliant polymeric substrates. 54,55 Unfortunately, only a limited number of studies have reported on the thermal [56][57][58][59] and mechanical 42,[60][61][62][63][64][65][66] properties of ALD highk dielectric materials, and the numerous reviews [2][3][4][5][6][7][8] of high-k dielectrics have focused primarily on the electronic structure and interfacial properties of high-k dielectrics from a CMOS device perspective. To the authors' knowledge, a clear correspondence between thermal/mechanical and electrical/optical properties for ALD high-k dielectrics has yet to be established.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The estimated ratio was calculated by using the individual compound growth per cycle, for Al 2 O 3 and SiO 2 of 1.7 and 0.6 Å per cycle, respectively, and an average of already reported film densities. [52][53][54] It was assumed that the whole opaline structure was homogeneously infiltrated, for further details refer to the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%